2018
DOI: 10.1021/acs.molpharmaceut.8b01117
|View full text |Cite
|
Sign up to set email alerts
|

Insight into Amorphous Solid Dispersion Performance by Coupled Dissolution and Membrane Mass Transfer Measurements

Abstract: The tendency of highly supersaturated solutions of poorly water-soluble drugs to undergo liquid–liquid phase separation (LLPS) into drug-rich and water-rich phases when the concentration exceeds the amorphous solubility, for example, during dissolution of some amorphous solid dispersions, is thought to be advantageous from a bioavailability enhancement perspective. Recently, we have developed a high surface area, flow-through absorptive dissolution testing apparatus that enables fast mass transfer providing mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 53 publications
(100 reference statements)
1
34
0
Order By: Relevance
“…This phenomenon describes a phase transition of a supersaturated solution into a drug-rich and solvent-rich phase [33]. The occurrence of nanoscale colloids or liquid-liquid phase separation can act as a reservoir for the supersaturation level as a result of rapid re-dissolution kinetics and it is also related to an enhanced absorption [33][34][35]. Consequently, the occurrence of that phenomenon can be considered as beneficial for an ASD upon dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon describes a phase transition of a supersaturated solution into a drug-rich and solvent-rich phase [33]. The occurrence of nanoscale colloids or liquid-liquid phase separation can act as a reservoir for the supersaturation level as a result of rapid re-dissolution kinetics and it is also related to an enhanced absorption [33][34][35]. Consequently, the occurrence of that phenomenon can be considered as beneficial for an ASD upon dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…10 Nevertheless, the formation of these colloidal species has been hypothesized to be beneficial for oral drug delivery, by serving as a reservoir and continuously replenishing the absorbed drug. 10,14 Diffusion through the unstirred water layer is often considered the ratelimiting step for intestinal uptake of highly permeable lipophilic compounds. [15][16][17] Therefore, particle drifting into the unstirred water layer, has also been suggested as a mechanism by which absorption is enhanced by colloidal drug aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum permeability then reaches a new plateau at a high apparent drug concentration. Experimentally, Siddhi et al demonstrated the dissolution performance and membrane mass transportation for atazanavir (ATZ) ASD using a high surface area apparatus [111]. Figure 5A illustrated the maximum drug concentration (C max ) and the area under the curve (AUC) values in the acceptor compartment in relation to the drug's apparent concentration in the donor compartment.…”
Section: The Roles Of Drug-rich Phase In Membrane Transportationmentioning
confidence: 99%
“…In contrast, polymers stabilizing the supersaturated drug solution without significantly affecting the thermodynamic activity may result in a better permeability enhancement. [111], American Chemical Society, 2018. (B) A comparison of the itraconazole in vivo data and permeability models with or without modified with the effect of nanoparticles in aqueous solution "drifting" into the ABL.…”
Section: The Importance Of Polymeric Excipients For Drug Permeability Enhancementmentioning
confidence: 99%